Recent Progress in Harvest and Recovery Techniques of Mammalian and Algae Cells for Industries - Tan C.H.; Nomanbhay S.; Shamsuddin A.H.; Show P.L. (Springer, 2023)
biofuel; endotoxin; immunoglobulin G; monoclonal antibody; polymer; agriculture; alga; biotechnology; centrifugation; Chlamydomonas; Chlorella; CHO cell line; chromatin; Coelastrella; continuous disk stack centrifugation; depth filtration; filtration; harvest; industry; ion exchange chromatography; mammal cell; microfiltration; Monoraphidium; Nannochloropsis; Review; tangential flow microfiltration; turbidity